Evidence for Preoperative Aspirin Improving Major Outcomes in Patients With Chronic Kidney Disease Undergoing Cardiac Surgery: A Cohort Study. Issue 1 (January 2015) - Yao, Linong; Young, Nilas; Liu, Hong; Li, Zhongmin; Sun, Will; Goldhammer, Jordan; Tao, Lei; He, Jianbin; Diehl, James; Sun, Jianzhong
Abstract : Background: Effects of aspirin on patients with chronic kidney disease (CKD) remains unclear. This study aimed to examine the effect of preoperative aspirin use on postoperative renal function and 30-day mortality in patients with CKD undergoing cardiac surgery. Methods: A retrospective cohort study was performed on consecutive patients (n = 5175) receiving cardiac surgery in 2 tertiary hospitals. Of all patients, 3585 met the inclusion criteria and underwent the analysis to determine the association of preoperative aspirin with incidence of acute kidney injury (AKI) and death based on estimated glomerular filtration rate (eGFR). Results: Of 3585 patients, 31.5% had CKD (eGFR < 60 mL/min/1.73 m 2 ) at baseline and 27.6% had AKI postoperatively. The baseline eGFR had a nonlinear relationship with the incidence and stages of AKI. As eGFR decreased to 15 to 30 from more than or equal to 90 mL/min/1.73 m 2, AKI and 30-day mortality increased to 50.5% from 23.5% and to 11.9% from 2.6%, respectively ( P < 0.001). However, preoperative aspirin use was associated with a significant decrease in postoperative AKI and 30-day mortality in patients with CKD undergoing cardiac surgery, in particular, the survival benefit associated with aspirin was greater in patients with CKD (vs normal kidney function): 30-day mortality was reduced by 23.3%, 58.2%, or 70.0% for patients with baseline eGFR more than or equal to 90, 30 to 59, or 15 to 30 mL/min/1.73 m 2, respectively ( P trend < 0.001). Conclusions: For patients with CKD undergoing cardiac surgery, preoperative aspirin therapy was associated with renal protection and mortality decline. The magnitude of the survival benefit was greater in patients with CKD than normal kidney function. Abstract : For patients with chronic kidney disease (CKD) undergoing cardiac surgery, this retrospective cohort study showed a close correlation among CKD, postoperative AKI, and adverse outcomes, whereas preoperative aspirin therapy was associated with renal protection and mortality decline. The magnitude of the survival benefit was greater in patients with CKD than normal kidney function.